A low complexity ofdm modulator/demodulator based on discrete hartley transform - Zakaria, Sembiring
The investigation upon to discrete Hartley transform (DHT) to replace the conventional complex-valued and mature discrete Fourier transform (DFT) as the OFDM modulator and demodulator was carried out in this research. The overall project is divided into two parts as follows: firstly, the proposed system is simulated under various parameters such as BER versus SNR and the quality of image versus given value of SNR. Secondly, the simulation model has been developed using excellent software for simulation, MATLAB. Statistically analysis has been investigated to measure the accuracy of the system performance and also the complexity of the system. Simulation results show that the system complexity is reduced in term of multiplication and addition number. For number of subcarriers, N = 64, 52 % of multiplication and 28 % of addition numbers are reduced. The system performance is measured in term of plotted graph of BER versus SNR and quality of received image versus SNR, where the BER value is 10-3 and quality of image is similar with the original image when the given value of SNR = 30 dB.